Autotaxin activity increases locally following lung injury, but is not required for pulmonary lysophosphatidic acid production or fibrosis. Issue 6 (22nd March 2016) - Black, Katharine E.; Berdyshev, Evgeny; Bain, Gretchen; Castelino, Flavia V.; Shea, Barry S.; Probst, Clemens K.; Fontaine, Benjamin A.; Bronova, Irina; Goulet, Lance; Lagares, David; Ahluwalia, Neil; Knipe, Rachel S.; et al.
ABSTRACT: Lysophosphatidic acid (LPA) is an important mediator of pulmonary fibrosis. In blood and multiple tumor types, autotaxin produces LPA from lysophosphatidylcholine (LPC) via lysophospholipase D activity, but alternative enzymatic pathways also exist for LPA production. We examined the role of autotaxin (ATX) in pulmonary LPA production during fibrogenesis in a bleomycin mouse model. We found that bleomycin injury increases the bronchoalveolar lavage (BAL) fluid levels of ATX protein 17‐fold. However, the LPA and LPC species that increase in BAL of bleomycin‐injured mice were discordant, inconsistent with a substrate‐product relationship between LPC and LPA in pulmonary fibrosis. LPA species with longer chain polyunsaturated acyl groups predominated in BAL fluid after bleomycin injury, with 22:5 and 22:6 species accounting for 55 and 16% of the total, whereas the predominant BAL LPC species contained shorter chain, saturated acyl groups, with 16:0 and 18:0 species accounting for 56 and 14% of the total. Further, administration of the potent ATX inhibitor PAT‐048 to bleomycin‐challenged mice markedly decreased ATX activity systemically and in the lung, without effect on pulmonary LPA or fibrosis. Therefore, alternative ATX‐independent pathways are likely responsible for local generation of LPA in the injured lung. These pathways will require identification to therapeutically target LPA production in pulmonary fibrosis.—Black, K. E., Berdyshev, E., Bain, G., Castelino, F. V., Shea, B. S., Probst, C. K., Fontaine, B. A., Bronova, I., Goulet, L., Lagares, D., Ahluwalia, N., Knipe, R. S., Natarajan, V., Tager, A. M. Autotaxin activity increases locally following lung injury, but is not required for pulmonary lysophosphatidic acid production or fibrosis. FASEB J. 30, 2435–2450 (2016). www.fasebj.org